Pengaruh Fungsi Audit Internal dan Pemanfaatan Teknologi Informasi Terhadap Kinerja Karyawan PT. Agung Prima Network - Nur Rahman, Zulvie; Suyanto, Suyanto; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2025)
This study aims to examine the influence of internal audit function and utilization of information technology on employee performance at PT. Agung Prima Network. This study uses a quantitative approach with a survey method using a questionnaire as a data collection instrument. The research sample was employees of PT. Agung Prima Network who were selected randomly. Data analysis was carried out using regression techniques to test the proposed hypothesis. The results of this study showed an Adjusted R Square value of 0.708. This shows that the relative contribution of the influence of the internal audit function (X1) and the use of information technology (X2) on employee performance at PT. Agung Prima Network is 70.8%. This shows that the internal audit function has a significant positive effect on employee performance. In addition, the use of information technology also has a significant positive effect on employee performance in this company. The practical implication is the importance of strengthening the internal audit function and investing in information technology to support the achievement of company goals through improving employee performance